Weed Control with Single or Sequential Herbicide Applications in Acetolactase Synthase-Tolerant Grain Sorghum - R. Currie; P. Geier (Kansas Agricultural Experiment Station Research Reports, 2016)
Palmer amaranth control was best when Resolve (rimsulfuron) plus Harmony GT (thifensulfuron) and Abundit Extra (glyphosate) were applied 15 days preplant followed by Zest (nicosulfuron) and atrazine postemergence, or by Zest plus atrazine alone postemergence. Palmer amaranth control was less than 80% with all other herbicide treatments. Preemergence herbicides alone provided less than 60% green foxtail control at 53 days after postemergence applications, and Zest plus atrazine alone postemergence controlled green foxtail 70%. Sequential applications of preemergence and postemergence herbicides were needed to provide the best green foxtail control. The relatively low weed control provided by these treatments may be partially explained by excessive precipitation and irrigation during the study.
Keywords: grain sorghum; acetolactase synthase-tolerant grain sorghum; weed control; Palmer amaranth; puncturevine; green foxtail; Resolve; Rimsulfuron; Harmony GT; Thifensulfuron; Abundit Extra; Glyphosate; Zest; Nicosulfuron; atrazine